Stenographic Approaches for Enhancing Data Security in Cloud Computing - Rajguru Sankalp Sudarsan; Singh Gursharan; Malhi Simarjit Singh; Kaur Gursimran (E3S Web of Conferences, 2024)
Steganography has become a well-known method for concealing data so that unauthorized users cannot identify it among other data. With the growing popularity of cloud computing, security of cloud databases has become a major problem, and the necessity to safeguard sensitive data stored in the cloud has become crucial. Cloud computing is an emerging technology that provides users with enormous storage and computational capabilities. In the modern world, cloud computing is become a necessary technology. Using the internet, individuals may remotely process, store, and access data. However, Security has become a major problem as more data is kept on the cloud. The difficulties in implementing steganography in cloud computing and suggest some future research areas in this area. Our review suggests that steganography can be a useful technique for strengthening the security of cloud databases, but its use calls for careful evaluation of the difficulties involved. Overall, the use of steganography techniques in cloud computing and their potential to improve the security of cloud databases are discussed in this study in useful details.